Sumbangan Antropologi dalam Penelitian Arkeologi - Taniardi, Putri Novita (BALAI ARKEOLOGI PAPUA, 2009)
Archaeology is a science that has goals to reconstruct the culture of the past, to reconstruct the culture history and reconstruct the changing of culture. To reach the goals, archaeology needs other field of science to help in analyzing the archaeological subject and Anthropology is one of them. The contribution of Anthropology in Archaeological research is particularly on its advantage in ethnographic data. Ethnoarchaeology is one of the branches of archaeology which using ethnographic analogy as one of the methods. Nevertheless, Ethnography should not just be interpreted as a data but also as a method. By applying the ethnographic method in archaeological research, it is hoped that it could help Archaeology in solving the problem they’re faced.